On generalized fuzzy strongly semiclosed sets in fuzzy topological spaces - Oya Bedre Ozbakir (International Journal of Mathematics and Mathematical Sciences)
We introduce the concept of generalized fuzzy strongly semiclosed, generalized fuzzy almost-strongly semiclosed, generalized fuzzy strongly closed, and generalized fuzzy almost-strongly closed sets. In the light of these definitions, we also define some generalizations of fuzzy continuous functions and discuss the relations between these new classes of functions and other fuzzy continuous functions.